Food safety aspects of fresh Nile perch (Lates niloticus) fillets from Lake Victoria imported to the European market: Helminth parasites and microbiological status. (August 2017) - Klapper, Regina; Meyer, Carsten; Kuhn, Thomas; Karl, Horst
Abstract: Nile perch ( Lates niloticus ) is a popular, usually low priced food fish in many countries worldwide, and the most important export fish from Lake Victoria and its adjacent countries Uganda, Tanzania and Kenya. Despite its high import figures, the constantly increasing demand within the EU for 'new' fish species and the results of initial studies indicating high coliform bacterial loads, food safety aspects regarding its microbiological as well as parasitological status have been hitherto widely neglected. In the present study imported fresh fish fillets as well as superchilled fish from a German retail market and a Dutch wholesaler were examined to evaluate the current microbiological and parasitological quality. A total of 200 fresh fillets as well as 20 superchilled fish (beheaded, eviscerated, descaled) samples were screened for the presence of helminth parasites by visual inspection, candling, the UV-press method and artificial digestion method. The study includes as well a quantitative test on the recovery rate of metacercarial cysts. Microbial assessment was performed on ten fresh fillets and on the skin and tissue of 20 superchilled fish. Helminth parasites were neither detected in the edible parts nor in the skin of imported products. Results of the microbiological examination revealed low levels of bacterial contamination of superchilled fish samples, whereas high total viable counts and high levels of naturally present bacterial pathogens of the genus Aeromonas spp. and Pseudomonas spp. were identified from the fresh fillets. Our findings indicate that hygienic production conditions have improved in comparison to previous studies. As total viable counts as well as specific spoiling bacteria were high in fresh fillets, we recommend adequate heat treatment of fresh Nile perch fillets before consumption. Highlights: Nile perch from Lake Victoria was examined for helminth parasites. The microbial quality was assessed from a subset of samples. No helminth parasites were found during a two-years sampling period. The microbiological quality indicated an improvement of hygienic conditions. Due to high viable bacteria counts (TVC), adequate heat-treatment is recommended.